PENGARUH LATIHAN PENGUATAN METODE DELORME DAN METODE OXFORD TERHADAP PENINGKATAN KEKUATAN OTOTQUADRICEP PADA SISWA DI SEKOLAH SEPAK BOLA KUDA PUTIH DI JALAN DENAI JERMAL 15 MEDAN TENGGARA VII - Mhd Ikhsan Nasution; Yeni Vera; Sulaiman Sulaiman (Journal of Health Science and Physiotherapy, 2021)
This study was to determine the effect of strengthening exercises and methods delorme oxford method to increase the strength of the quadriceps muscle Football School students the White Horse in the field Tenggara. Sampel Denai Jermal 15 consists of 24 students of the school football White Horse , the patient. The studywas conducted for 4 weeks , starting from May 13 - June 23, 2015 .The type of quasi experimental research or Quasi experiment . The study design used is a pre and post test design.Tehnik sampling by non- probability sampling , with purposive sampling method . Data processing and data analysis using t -test Independent test . Results : ( 1 ) strengthening exercises Delorme method is very useful to the improvement of quadriceps muscle strength , statistical tests Independent t - test paired t -test showed that the p value is 0.000 , which means p-value < 0.05 as the average of quadriceps muscle strength before treatment methods dolorme was 22.92 and after 24.62 with 0.450 SD obtain the mean difference 1.70 , the hypothesis in this study be accepted. ( 2 ) strengthening exercises oxford very useful method to increase quadriceps muscle strength , statistical tests Independent t - test paired t -test showed that the p value is 0.000, which means p value < 0.05 as the average of quadriceps muscle strength before treatment methods oxford is 23 , 25 and after 25.00 with a difference of 1.75 SD 0.866 get the hypothesis in this study be accepted. ( 3 ) No significant effect of both methods Delorme and Oxford to the increase in quadriceps muscle strength at students in SSBKP at Medan Denai, because the average Delorme method quadriceps muscle strength after treatment was 24.62 and the Oxford method was 25.00 with SD 1,464 results dependent test sample t -test Paired t -test showed that significant p value 0.394 p value > 0.05 then the hypothesis in this study was rejected .